Analyzing the Efficiency and Profitability Determinants: Evidence from Chinese Banks, 2009 to 2014 - LIN, NAN (2015)
This study aims to investigate the efficiency and determinants of bank profitability from 2009-2014 by selecting 29 Chinese commercial banks. The distinction of this study is that we use two-stage analysis method. In this first stage, stochastic frontier approach (SFA) is used to measure the bank’s x- efficiency. As in the second stage, system GMM regressors are used to measure the determinants of Chinese bank profitability. All the determinants are classified into two groups, internal variables and external variable. The result in this study implies that different ratio will have different effect on banks’ performance.